Decentralization and Public Accountability: Evaluating Legal Frameworks of Local Governance Performance in Southeast Asia - Aswanto Aswanto; Teddy Delano; Azka Syifaul Maula (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the relationship between decentralization and public accountability through an empirical normative legal analysis of local governance frameworks in Southeast Asia. The research integrates doctrinal legal interpretation with comparative governance evaluation in order to assess the effectiveness of constitutional regulation fiscal decentralization and digital governance within decentralized administrative systems. Primary legal materials consist of constitutional provisions regional governance statutes judicial decisions and ASEAN institutional instruments while empirical evidence is derived from Worldwide Governance Indicators transparency reports and official governmental publications concerning local governance performance. The findings demonstrate that decentralization strengthens democratic participation and regional administrative flexibility although fragmented regulatory structures uneven institutional capacity and inconsistent fiscal supervision continue to weaken accountability performance across local governments. Fiscal decentralization contributes to regional economic development and governmental responsiveness yet simultaneously increases corruption risks budgetary opacity and supervisory complexity within multilevel governance systems. The study further identifies that digital governance transformation and hybrid administrative coordination require adaptive legal frameworks capable of integrating transparency institutional supervision and technological accountability in order to preserve democratic legitimacy and effective public administration within Southeast Asian decentralized governance systems.